Impact of a telephone-first consultation system in general practice. Issue 1129 (20th July 2019) - Miller, Diane; Loftus, Angela M; O'Boyle, Peter J; McCloskey, Martin; O'Kelly, John; Mace, Donna; McKeon, Neil; Ewan, Sian-Lee; Moore, Laura; Abbott, Aine; Cunning, Shane; McCarron, Mark O; et al.
Abstract: Purpose of the study: Increasing pressure on general practice prompts innovative change in service organisation. This study sought to evaluate the impact of introducing a telephone-first consultation system in a socioeconomically deprived population. Study design: An interrupted time series of preplanned outcomes for 2 years before and 1 year postintroduction of a telephone-first system was used to measure the volume and type of general practitioner (GP) consultations and the number of patients consulted per year. Emergency department (ED) and GP out-of-hours attendances, the number of outpatient referrals, and the number of requests for laboratory tests were measured as secondary outcomes. Results: The telephone-first system was associated with a 20% increase in total GP consultations (telephone and face-to-face, effect estimate at 12 months, p=0.001). Face-to-face consultations decreased by 39% (p<0.001), while telephone consultations increased by 131% (p<0.001). The volume of individual patient requests for a GP consultation and the number of treatment room nurse consultations did not change. Secondary outcome measures showed no change in hospital outpatient referrals, number of requests for laboratory tests, and ED or GP out-of-hours attendances. Conclusions: A telephone-first system in a deprived urban general practice can decrease delays to GP–patient contacts. The number of patients seeking a medical intervention did not differ irrespective of the consultation system used. The telephone-first system did not affect GP out-of-hours, laboratory investigations or secondary care contacts.